Substance and Accidents: Views and Developments from the Late Middle Ages to the Modern Age. Presentation - Luise, Gennaro; Petagine, Antonio (Acta Philosophica, 2022)
Substance and Accidents: Views and Developments from the Late Middle Ages to the Modern Age Gennaro Luise, Antonio Petagine, Presentation Joël Biard, La matière est-elle le sujet des accidents ? Un débat au XIVe siècle Hervé Pasqua, L’Un sans l’être: métaphysique, méontologie et infinité chez Nicolas de Cues Yitzhak Y. Melamed, The Banishment of Accidents from Spinoza’s Paradise Antonio Petagine, Congedarsi da Aristotele: John Locke e le nozioni di sostanza e accidente Dario Sacchi, Il “Rapporto della sostanzialità” in Hegel